Student use of communication technologies-parent/guardian survey report - Julka, Ashley; Stehr, Grady; Parks, Denise; Trechter, David (My University, 2010)
The purpose of this study was to gain a better understanding of how middle school students and their parents are using technologies and what programs citizens of Wisconsin might need with respect to these technologies.
19 p.
Keywords: Communication; Internet--Safety measures; Online social networks; Technology and children; Internet and children; Texting; Text messages (Telephone systems)